Penerapan Sistem Attachment Pada Anak Melalui Gawai - Sekar, Dwi Amalia Chandra; Layyinah, Aqilatul (UI Scholars Hub, 2020)
Attachment between mother and child is an affective bond that is important to maintain in a family. For working mothers, the device is one solution to maintain attachment to their children. This research aims to describe the attachment system in children aged 2-3 years through the device and the application of the attachment system to fulfill the developmental tasks of the child. The articles are arranged based on qualitative research with descriptive methods. Although the attachment system that was built was adapted to the use of the device, but working mothers always maintain the quality of their relationship by interacting with children while at home. The attachment system can be used to help fulfill the child's developmental tasks according to their age. Because in its implementation, the fulfillment of child development tasks involves all parties who interact with the child's environment both directly and indirectly. If this cycle of interaction occurs repeatedly and is continuously carried out by parents to answer the child's needs, then the child's rights can be fulfilled. If the children's rights and needs in supporting the child's developmental tasks in accordance with their age can be fulfilled, then the child's welfare can be realized. This study suggests that parents who work increase awareness to always regulate the use of devices, introduce digital literacy to children, supervise and assist children, and manage attachments with children directly outside working hours.